NELAYAN TIKU: TRADISI DAN KELEMBAGAAN SOSIAL BERDASARKAN BUDAYA MASYARAKAT LOKAL BERBASIS KOMUNITAS DALAM AKTIVITAS PENANGKAPAN IKAN - Lucky Zamzami (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
This article based on the results of research conducted at one of the villages the coastal areas of West Sumatra, in Nagari Tiku Selatan, Tanjung Mutiara District, Agam. This area have been based on traditions since ancestors held as tradition " “membangun rumpon”, “festival Babantai and “Tolak Bala”. The role of social institutions that have been rooted in self in Tiku fishermen whose presence is needed by the community. Social institutions set up in the form of “Arisan” association (Julo-Julo), followed by wives of fishermen, Religious tradition (Yasinan), Social Death tradition, mutual assistance are bottom up. This institute aims to improve the socio-economic members and provide a sense of security and safety in public life consistently carry out its consistent activities on a regular activities.